Japan's Changing Industrial Landscape - Yusuf, Shahid; Nabeshima, Kaoru (World Bank, Washington, DC, 2012)
This paper explores various strategic options available to Japanese firms faced with the increasing market pressures in the global economy. Whether Japanese firms are able to retain the competitive edge will depend on the continuing gains in their manufacturing capability, their capacity to exploit and adapt to changing market circumstances, and innovativeness at many levels. The authors discuss six main developments that are changing the industrial landscape in Japan and in this context, they explore the nature of the responses required of firms and examine some implications of the measures adopted for the Japanese economy as a whole.